(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The concept of Corporate Social Responsibility (CSR) is not at all new in India. Corporate social responsibility (CSR) is an upcoming buzzword worldwide. The concept ’Corporate Social Responsibility’ (CSR) also refers to ’soft’, voluntary self regulation which is adopted by firms to actually improve various aspects of the company, this can be related to labour, environmental and even human rights issues In today‘s globalized world, there it is one of the greatest challenges faced by firms and that is integration of CSR in business. Many stakeholders actually require a lot more from the other companies than merely actually pursuing the growth and its profitability. CSR has actually become a long way in India and its sustainability in other emerging markets. From these responsive activities to sustainable initiatives, even corporates have clearly exhibited itself with their ability to make a significant difference in the society and also to improve the overall quality of life. It focuses on the concept of CSR, its various dimensions along with sustainability and its relevance in emerging markets in India.